2016
DOI: 10.1038/srep35479
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of factors underlying the metabolic shifts in developing kernels of colored maize

Abstract: Elucidation of the metabolic pathways determining pigmentation and their underlying regulatory mechanisms in maize kernels is of high importance in attempts to improve the nutritional composition of our food. In this study, we compared dynamics in the transcriptome and metabolome between colored SW93 and white SW48 by integrating RNA-Seq and non-targeted metabolomics. Our data revealed that expression of enzyme coding genes and levels of primary metabolites decreased gradually from 11 to 21 DAP, corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 64 publications
(86 reference statements)
2
16
1
Order By: Relevance
“…This discrepancy was confirmed by previous transcriptome analyses: The expression of Vp1 is initiated at ;3 to 5 DAP, reaches a peak at ;10 DAP, and gradually decreases thereafter until the end of grain filling (Supplemental Figure 8; Chen et al, 2014;Meng et al, 2018;Yi et al, 2019). By contrast, C1 and Em genes begin to express from ;12 to 15 DAP (McCarty et al, 1991;Hu et al, 2016), and Glb1 and Glb2 are increased in expression from ;20 DAP (Figure 2; Supplemental Figure 8). The discrepant temporal-expression trends among these genes suggest that perhaps some unknown factors rather than VP1 directly promote initiation of C1, Em, and Glbs expression.…”
Section: Transactivation Effects Of Vp1 On Glb1 and Other Embryo-exprsupporting
confidence: 74%
“…This discrepancy was confirmed by previous transcriptome analyses: The expression of Vp1 is initiated at ;3 to 5 DAP, reaches a peak at ;10 DAP, and gradually decreases thereafter until the end of grain filling (Supplemental Figure 8; Chen et al, 2014;Meng et al, 2018;Yi et al, 2019). By contrast, C1 and Em genes begin to express from ;12 to 15 DAP (McCarty et al, 1991;Hu et al, 2016), and Glb1 and Glb2 are increased in expression from ;20 DAP (Figure 2; Supplemental Figure 8). The discrepant temporal-expression trends among these genes suggest that perhaps some unknown factors rather than VP1 directly promote initiation of C1, Em, and Glbs expression.…”
Section: Transactivation Effects Of Vp1 On Glb1 and Other Embryo-exprsupporting
confidence: 74%
“…In Brunfelsia acuminata , the expression of BaCHS was positively correlated with petal anthocyanin contents [39]. In a maize cultivar, ‘SW93′ (purple kernels), two CHSs were upregulated along the kernel as the color deepened and anthocyanins accumulated [40]. In C. sinensis , high CHS transcript values were associated with a high amount of total tea polyphenols and total catechin [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…The integration of transcriptomic data revealed that kinetic trends in the transcriptome and metabolome were similar across kernel development. An important metabolic shift from the primary to the secondary metabolism occurred at 16 DAP only in the purple pigmented kernel targeting the biosynthesis of anthocyanins and precursors of phlobaphenes [113]. The biochemical information generated in above studies would be valuable in molecular breeding strategies aimed at increasing health promoting metabolites such as anthocyanins in corn kernel.…”
Section: Use Of Non-targeted Metabolomic Platforms For the Research Omentioning
confidence: 99%
“…Hu et al [ 113 ] studied the metabolome of purple pigmented and non-pigmented kernels from China at different maturity stages (11, 16, 21 days after pollination (DAP)) using a combination of LC-MS/MS and GC-MS. A total of 247 metabolites were identified and metabolomes differed according to the maturity stage. The integration of transcriptomic data revealed that kinetic trends in the transcriptome and metabolome were similar across kernel development.…”
Section: The Application Of Metabolomics For the Characterization mentioning
confidence: 99%